Intelligent Car Parking Application Using Android Studio and Machine Learning - Telugu Maddileti, Shishir Kondai, Vytla Santosh Kumar (International Journal of Advanced Science and Technology, 2020)
This project intends to provide users with a solution to save time by reserving a parking slot for them via an android application. The resources related to the app are hosted in the AWS cloud. The app contains a login and register page, where users have to fill in their details to use the app and confirm it by email where multi factor authentication is implemented and later login with those credentials .The data related to login is also attributed and stored with device key, IP address and SDK version of application used. Following it, the application provides information about the parking slots available, so that they do not waste time finding a spot inside. If the user wishes to reserve a slot, he/she must provide the details like name, vehicle registration number and mobile number before confirming the booking. Customers can also view their bookings in the bookings tab of the android application. Using machine learning, the admin can make changes to the parking slots availability without manually checking for slots, checking for the intruders and alerting the administrator and, Conversion of the speech to text from the recorded audio at camera, by using the services like AWS Rekognition service, AWS Transcribe, AWS API Gateway, AWS Lambda, AWS SNS and related AWS Services. The model is trained with images of parking slots with and without cars and thus returns the output as occupied or empty at specific slots. Keywords: car parking, android studio, parking reservation, machine learning, AWS Sage Maker, AWS Recognition service, AWS Transcribe, AWS API Gateway.